Situation Report: Czechoslovakia, 17 March 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Regional Conference: Normalization Continues The Institute of Nuclear Research at Rez Slow Progress in Superhighway Construction